Pengendalian Intern Piutang Usaha Pada PT. Bank Tabungan Negara (Persero), Tbk Cabang Manado - Reginaldo J. K. Sigar; Dolina L. Tampi; Lucky F. Tamengkel (Universitas Sam Ratulangi, 2018)
The Bank is a financial institution that functions to collect funds from the public in the form of deposits and then redistributes them in the form of credit. In carrying out internal control of trade receivables, what must be the center of attention is how safeguards that will be efficient and effective are carried out on trade receivables, both in terms of security that will be efficiently and effectively carried out on trade receivables, both in terms of security of physical cash gains, separation assignment, until the availability of accurate accounting records data. Internal control is all organizational plans, methods, and measurementschosen by business activities to secure their assets, check accuracy and reliability of business accounting data, improve operational efficiency, and support compliance with policies Managerial that has been determined. This study aims to determine the benefits of internal trade receivables control at PT. Bank Tabungan Negara (Persero) Tbk ManadoBranch. The object of this study is PT. Bank Tabungan Negara (Persero) Tbk Manado Branch located in Manado, North Sulawesi, Indonesia. This study uses qualitative descriptive analysis method, namely by collecting data directly from the company by observing, interviewing according to the research subject. The results of the research show that from the elements of internal control according to the COSO framework, it has been running well. Internal control of trade receivables at PT. Bank Tabungan Negara (Persero) Tbk Manado Branch has run well, competent employees, and a small amount of uncollectible accounts. Keywords: Internal Control, Accounts Receivable.